Guideline adherence for identification and hydration of high-risk hospital patients for contrast-induced nephropathy - Schilp, Janneke (BioMed Central, 2014)
BACKGROUND: Contrast-induced nephropathy (CIN) is a common cause of acute renal failure in hospital patients. To prevent CIN, identification and hydration of high-risk patients is important. Prevention of CIN by hydration of high-risk patients was one of the themes to be implemented in the Dutch Hospital Patient Safety Program. This study investigates to what extent high-risk patients are identified and hydrated before contrast administration. Hospital-related and admission-related factors associated with the hydration of high-risk patients are identified. METHODS: The adherence to the guideline concerning identification and hydration of high-risk patients for CIN was evaluated retrospectively in 4297 patient records between November 2011 and December 2012. A multilevel logistic regression analysis was used to investigate the association between hospital-related and patient-related factors and hydration. RESULTS: The mean percentage patients with a known estimated Glomerular Filtration Rate before contrast administration was 96.4%. The mean percentage high-risk patients for CIN was 14.6%. The mean percentage high-risk patients hydrated before contrast administration was 68.5% and was constant over time. Differences between individual hospitals explained 19% of the variation in hydration. The estimated Glomerular Filtration Rate value and admission department were statistically significantly associated with the execution of hydration. CONCLUSION: The identification of high-risk patients was almost 100%, but the subsequent step in the prevention of CIN is less performed, as only two third of the high-risk patients were hydrated before contrast administration. Large variation between individual hospitals confirmed the difference in hospitals in correctly applying the guideline for preventing CIN.